2022
DOI: 10.1016/j.ijid.2021.12.321
|View full text |Cite
|
Sign up to set email alerts
|

No difference in risk of hospitalization between reported cases of the SARS-CoV-2 Delta variant and Alpha variant in Norway

Abstract: Objectives To estimate the risk of hospitalisation among reported cases of the Delta variant of SARS-CoV-2 compared to the Alpha variant in Norway. We also estimated the risk of hospitalisation by vaccination status. Methods We conducted a cohort study on laboratory-confirmed cases of SARS-CoV-2 in Norway, diagnosed between 3 May and 15 August 2021. We calculated adjusted risk ratios (aRR) with 95% confidence intervals (CIs) using multivariable log-binomial regression, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…To these series we apply a risk of hospitalisation for the Omicron BA.1 variant of 1.5551%. This was obtained as follows: r o = 0.33 × 1 × 4.7% = 1.551%, where 0.33 is the hazard ratio of Omicron relative to Delta (UKHSA, 2021), 1 is the hazard ratio of Delta relative to Alpha (Veneti et al, 2022) and 4.7% is the adjusted absolute risk of hospital admission for the Alpha variant (Nyberg et al, 2021). Then, and give the hospitalised infected non-vaccinated and hospitalised infected vaccinated, where ve hosp | infection,t is the vaccine effectiveness against hospitalisation conditioned on infection which (following Viana et al, 2021, equation (14)) can be obtained from: with the difference that the vaccine protection wanes, where ve infection is the vaccine efficacy against infection for the Omicron BA.1 variant, ve hosp is the vaccine efficacy against hospitalisation and w in,t is the waning of the vaccines protection against infections.…”
Section: Resultsmentioning
confidence: 99%
“…To these series we apply a risk of hospitalisation for the Omicron BA.1 variant of 1.5551%. This was obtained as follows: r o = 0.33 × 1 × 4.7% = 1.551%, where 0.33 is the hazard ratio of Omicron relative to Delta (UKHSA, 2021), 1 is the hazard ratio of Delta relative to Alpha (Veneti et al, 2022) and 4.7% is the adjusted absolute risk of hospital admission for the Alpha variant (Nyberg et al, 2021). Then, and give the hospitalised infected non-vaccinated and hospitalised infected vaccinated, where ve hosp | infection,t is the vaccine effectiveness against hospitalisation conditioned on infection which (following Viana et al, 2021, equation (14)) can be obtained from: with the difference that the vaccine protection wanes, where ve infection is the vaccine efficacy against infection for the Omicron BA.1 variant, ve hosp is the vaccine efficacy against hospitalisation and w in,t is the waning of the vaccines protection against infections.…”
Section: Resultsmentioning
confidence: 99%
“…When considering the Delta variant, two UK community analyses found that Delta (or an S-gene proxy) infections were associated with a higher risk of admission to hospital than with Alpha[28,29]. Comparable results were observed in Danish, US, and Canadian populations with a study in a Norwegian population being the exception[30-33]. The US and Canadian studies also found that Delta was associated with increased risk of ICU admission and death[31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adjustment for differences in confounding variables, such as age, are required for effective estimation of the true effect 4 . Five studies 59 included estimates for both vaccinated and unvaccinated individuals. Three studies 10–12 were identified with known vaccination status from which the hospitalisation risk of Delta could be extracted only for the unvaccinated.…”
Section: Main Textmentioning
confidence: 99%